An exploration on integration of "Curriculum Ideological and Political Education" into senior high school English course - Dandan, Li; Noordin, Nooreen; Ismail, Lilliati; Wenling, Li (Human Resource Management Academic Research Society, 2023)
This study discusses the significance and methods of integrating curriculum ideological and political education in to senior high school English course in China. This article is divided into six parts, namely the introduction, literature review, the significance and methods of integrating curriculum ideological and political education into senior high school English curriculum, the practice of integrating curriculum ideological and political education into senior high school English curriculum, evaluation of effects, and conclusion and outlook. Firstly, the teaching methods and contents of senior high school English curriculum, as well as the concept and importance of curriculum ideological and political education in the curriculum will be introduced in the literature review. Secondly, how to integrate the concept of curriculum ideological and political education into senior high school English curriculum will be explored. Thirdly, specific case studies will be provided in the practice of integrating curriculum ideological and political education into senior high school English curriculum, and then evaluate the practical effects. The achievements of this research will be summarized in the conclusion and outlook at last. Through the research and exploration of this article, the author hope to provide educators with more systematic and practical teaching methods and guidance, and further improve the teaching quality of senior high school English curriculum and the comprehensive qualities of student.